Creencias de los estudiantes en los procesos de aprendizaje de las matemáticas - Chaves Esquivel, Edwin (2010)
This paper describes the influence that students’ beliefs have in regard to mathematics education. First, a theoretical review about the topic is done and then the results of researches in others contexts are analyzed. The results indicate that the students perceive Mathematics as a useful discipline but difficult, learned by exercise repetition. Their beliefs about Mathematics are the result of different experiences lived through school.